Cytotoxic analysis of ZnO and TiO2 nanoparticles : dual particle study - Xia, Qian. (2013)
Due to the advance application of nanomaterial within the last decade, TiO2 and ZnO nanoparticles have gained popularity in sunscreen market as a result of their excellent UV adsorption property and transparent appearance in cosmetic products. All the studies to date have only been conducted on either type of nanoparticle to investigate the toxicity on human skin. However the majority of modern sunscreen formulations contain both types of nanoparticles and therefore it is of great significance to study the combined effect of both nanoparticles on human skin. This study has investigated dual particle effect of TiO2 and ZnO nanoparticles on human dermal fibroblasts. It starts with single particle cytotoxicity assessment to determine the test concentrations for TiO2 and ZnO respectively. Results from dual particle assay have suggested hitherto an anagotistic effect between these nanoparticles and conclusions have been made based on diffusion and aggregation processes. Eventually this study will summarize dual particle interactions within a practical concentration range.